The Oxford Handbook of Social Media and Music Learning 2020
DOI: 10.1093/oxfordhb/9780190660772.013.35
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing Vulnerability to Develop Pedagogical Change Through MOOC Participation and Public Blogging

Abstract: Despite several decades of ground-breaking achievements in music education research and practice, the discipline’s status continues to stagnate, especially among our children and our governments. To address this stagnation, in 2016 the University of Sydney launched an internationally available Massive Open Online Course (MOOC) titled “The Place of Music in 21st-Century Education.” The intent of offering this course was to provoke critical thinking among music educators in order to break the cultural cycle that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In line with Wang and Woo (2010), the nature of reflective public blogging was a great stimulus for CT, because their thoughts were being shared with a broader audience. While, as expected (Giarré & Jaccheri, 2008), some participants did find this challenging, the addition of peer-review of blog posts created a community of practice (Wenger, 1998; further contextualised for this study in Humberstone et al, 2020) within that public forum (Zandi et al, 2014) which was, as has been shown, extremely stimulating for many participants, whichever side of the ideological fences they 'sat'. There is initial evidence that because the provocations took place within this community, change was able to begin to take place (Kahan, 2012).…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…In line with Wang and Woo (2010), the nature of reflective public blogging was a great stimulus for CT, because their thoughts were being shared with a broader audience. While, as expected (Giarré & Jaccheri, 2008), some participants did find this challenging, the addition of peer-review of blog posts created a community of practice (Wenger, 1998; further contextualised for this study in Humberstone et al, 2020) within that public forum (Zandi et al, 2014) which was, as has been shown, extremely stimulating for many participants, whichever side of the ideological fences they 'sat'. There is initial evidence that because the provocations took place within this community, change was able to begin to take place (Kahan, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…Boler, 1999;Bozalek et al, 2013;Mills, 1998;Postman, 2009;Trifonas, 2003). Each week we juxtaposed two examples of evidence-based literature that promoted differing solutions to a music education problem, but prevented simplistic, dichotomic thinking, such as learners facilely classifying one as 'right' and the other as 'wrong' (Humberstone et al, 2020).…”
Section: Intervention Procedures: Paedagogies Of Provocationmentioning
confidence: 99%
See 3 more Smart Citations